Braxton Bragg and Confederate defeat. - Hallock, Judith Lee, 1940- (University of Alabama Press, 1991)
In the Summer of 1863, Confederate General Braxton Bragg was commander of the Army of Tennessee, still reeling from its defeat in January at Murfreesboro, Tenn.
Vol. 2 Originally presented as the author's thesis (doctoral)--State University of New York at Stony Brook.
Keywords: Bragg, Braxton, -- 1817-1876.; Confederate States of America. -- Army -- Biography.; Bragg, Braxton, -- 1817-1876; Confederate States of America. -- Army; Generals -- Confederate States of America -- Biography.; Généraux -- États confédérés d'Amérique -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY.; Generals; United States -- Confederate States of America; Biographies; Biographies.